Oxysterols and apolipoproteins in multiple sclerosis: a 5 year follow-up study[S] - Fellows Maxwell, Kelly; Bhattacharya, Sonia; Bodziak, Mary Lou; Jakimovski, Dejan; Hagemeier, Jesper; Browne, Richard W.; Weinstock-Guttman, Bianca; Zivadinov, Robert; Ramanathan, Murali (Journal of lipid research, 2019)
The purpose of this work was to investigate whether changes in oxysterol and apolipoprotein levels over 5 years are associated with disease course and disability progression in multiple sclerosis (MS). This study included 139 subjects [39 healthy controls (HCs), 61 relapsing-remitting MS (RR-MS) patients, and 39 progressive MS (P-MS) patients]. Oxysterols [24-hydroxycholesterol (24HC), 25-hydroxycholesterol (25HC), 27-hydroxycholesterol (27HC), 7α-hydroxycholesterol (7αHC), and 7-ketocholesterol (7KC)] were measured at baseline and 5 years using a novel mass spectrometric method, and apolipoproteins were measured using immunoturbidometric diagnostic kits. Levels of 24HC (P = 0.004), 25HC (P = 0.029), and 27HC (P = 0.026) increased in P-MS patients. 7KC (P = 0.047) and 7αHC (P = 0.001) levels decreased in RR-MS patients, and there were no changes in any oxysterols in HCs. In MS patients, ApoC-II (all P ≤ 0.01) and ApoE (all P ≤ 0.01) changes were positively associated with all oxysterol levels. Increases in 24HC (P = 0.038) and ApoB (P = 0.038) and decreases in 7KC (P = 0.020) were observed in RR-MS patients who converted to secondary P-MS (SP-MS) at follow-up and in SP-MS patients compared with RR-MS patients. Oxysterols and their associations with apolipoproteins differed between MS patients and HCs over 5 years. Oxysterol and apolipoprotein changes were associated with conversion to SP-MS.